Stabilization of the floating sternocostal segment of the chest with multiple bilateral fractures of the ribs and the manubrium of the sternum - I. I. Kotov; E. N. Degovtsov; M. A. Sadyrin; D. A. Kalinichenko (Acta Biomedica Scientifica, 2022)
Among patients with floating rib fractures without pneumo- and hemopneumothorax or after their elimination, the most severe disorders of ventilation and circulation occur in patients with multiple bilateral rib fractures and a fracture of the sternum manubrium with the formation of a floating sternocostal segment of the chest. At the same time, the suction aero- and hemodynamic function of the chest is disturbed, there is pressure on the heart and large vessels. As a result, the efficiency of external respiration progressively decreases, the respiratory muscles are exhausted, which requires an urgent transfer to artificial ventilation of the lungs. The article presents a clinical case of successful treatment of such a chest injury using the author’s technique (Patent No. 2621871 of the Russian Federation). The extrathoracic silicone reinforced splint has two horizontal branches that go around the mammary glands. The splint is attached to the floating sternocostal segment with ligatures passed behind the sternum and laterally – to stable sections of the ribs along the posterior axillary line on both sides. The tire reliably holds the sternocostal segment from paradoxical movements. The tire is removed after 3  weeks. By this time, fibrous calluses are formed in places of fractures of bones and cartilage, and the swelling of the chest wall subsides. Superficial bedsores in the places of fixation of the splint are epithelialized under the scab within 7–8 days. The patient was examined a year later, her condition was satisfactory, she had no complaints, there was no chest deformity. The technique is less traumatic, it is indicated for patients with polytrauma and in other cases.